Advertising in the area of information. A perfect symbiosis around consumerism - Pellicer Jordá, María Teresa (Escribanía, 2018)
This text reflects on the role of advertising and journalism as means of communication and as a complementary pair regarding the formation of models of learning and behavior. It is questioned by the effects of both cases on the re-construction of social imaginaries that both create a consumption-dependent mass culture through the support of advertising (sell-inform). Journalism and advertising, as mass media, become actors with power that have an effect on the production process of contemporary culture to influence the daily lives of individuals